2022
DOI: 10.3390/cancers14205090
|View full text |Cite
|
Sign up to set email alerts
|

miR-214-Enriched Extracellular Vesicles Released by Acid-Adapted Melanoma Cells Promote Inflammatory Macrophage-Dependent Tumor Trans-Endothelial Migration

Abstract: The understanding of the molecular mechanisms leading to melanoma dissemination is urgently needed in view of the identification of new targets and the development of innovative strategies to improve patients’ outcomes. Within the complexity of tumor intercellular communications leading to metastatic dissemination, extracellular vesicles (EV) released by tumor cells are central players. Indeed, the ability to travel through the circulatory system conveying oncogenic bioactive molecules even at distant sites ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Extensive literature demonstrates how extracellular lactic acidosis sustains tumor progression by acting either directly on cancer cells, or indirectly, by reprogramming the stromal component within the tumor mass to guarantee cancer cell proliferation and survival even under prohibitive and hostile conditions. Briefly, the acidic TME promotes, on the one hand, the acquisition by cancer cells of high plasticity that renders them extremely adaptable to various scenarios they may encounter [ 10 ]; on the other one, extracellular acidosis is able to induce a pro-tumoral reprogramming in the stromal cells, for instance, by altering the capacity of natural and adaptive immune cells to face with the tumor [ 5 , 7 , 17 ], or by remodeling the vasculature rendering vessels more permeant and subsequently permissive to cancer cell intra/extravasation [ 33 ], or further, by inducing the generation of CAFs with all the pro-tumoral activity they are endowed with [ 12 ]. What is still not known, is the effect that the acidic TME may exert on the adipocyte compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature demonstrates how extracellular lactic acidosis sustains tumor progression by acting either directly on cancer cells, or indirectly, by reprogramming the stromal component within the tumor mass to guarantee cancer cell proliferation and survival even under prohibitive and hostile conditions. Briefly, the acidic TME promotes, on the one hand, the acquisition by cancer cells of high plasticity that renders them extremely adaptable to various scenarios they may encounter [ 10 ]; on the other one, extracellular acidosis is able to induce a pro-tumoral reprogramming in the stromal cells, for instance, by altering the capacity of natural and adaptive immune cells to face with the tumor [ 5 , 7 , 17 ], or by remodeling the vasculature rendering vessels more permeant and subsequently permissive to cancer cell intra/extravasation [ 33 ], or further, by inducing the generation of CAFs with all the pro-tumoral activity they are endowed with [ 12 ]. What is still not known, is the effect that the acidic TME may exert on the adipocyte compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The Lactate Colorimetric Assay Kit (BioVision, purchased from Vinci-Biochem, Florence, Italy) was used according to the manufacturer's instructions to measure lactate production in the conditioned media of GC cells, as previously described [18].…”
Section: Lactatementioning
confidence: 99%
“…A high TAM infiltration often leads to poor clinical outcomes in a great number of tumors, including melanoma (67,83,84). Besides, extracellular acidosis is another crucial aspect of the TME and Andreucci et al (85) observed that the acidic microenvironment stimulated the secretion of melanoma-EVs enriched with miR-214. Then, these EVs tended to induce a proinflammatory activation of macrophages by increasing the expression of COX-2 and the release of inflammatory cytokines, such as IL-1b, IL-6, TNF-a, and NO, so as to establish an inflammatory TME which in turn facilitated the progression of melanoma.…”
Section: Evs With Tammentioning
confidence: 99%